Pyrolysis Kinetic Behaviour of Glass Fibre-Reinforced Epoxy Resin Composites Using Linear and Nonlinear Isoconversional Methods - Samy Yousef (Polymers, 2021)
Due to the increasing demand for glass fibre-reinforced epoxy resin composites (GFRC), huge amounts of GFRC waste are produced annually in different sizes and shapes, which may affect its thermal and chemical decomposition using pyrolysis technology. In this context, this research aims to study the effect of mechanical pre-treatment on the pyrolysis behaviour of GFRC and its pyrolysis kinetic. The experiments were started with the fabrication of GFRC panels using the vacuum-assisted resin transfer method followed by crushing the prepared panels using ball milling, thus preparing the milled GFRC with uniform shape and size. The elemental, proximate, and morphology properties of the panels and milled GFRC were studied. The thermal and chemical decomposition of the milled GFRC was studied using thermogravimetric coupled with Fourier-transform infrared spectroscopy (TG-FTIR) at different heating rates. Meanwhile, the volatile products were examined using TG coupled with gas chromatography–mass spectrometry (GC-MS). The TG-FTIR and TG-GC-MS experiments were performed separately. Linear (Kissinger–Akahira–Sunose (KAS), Flynn–Wall–Ozawa (FWO), and Friedman) and nonlinear (Vyazovkin and Cai) isoconversional methods were used to determine the pyrolysis kinetic of the milled GFRC based on thermogravimetry and differential thermal gravimetry (TG/DTG). In addition, the TG/DTG data of the milled GFRC were fitting using the distributed activation energy model and the independent parallel reactions kinetic model. The TG results showed that GFRC can decompose in three stages, and the main decomposition is located in the range 256–500 °C. On the other hand, aromatic benzene and a C-H bond were the major functional groups in the released volatile components in FTIR spectra, while phenol (27%), phenol,4-(1-methylethyl) (40%), and p-isopropenylphenol (34%) were the major compounds in GC-MS analysis. Whereas, the kinetic results showed that both isoconversional methods can be used to determine activation energies, which were estimated 165 KJ/mol (KAS), 193 KJ/mol (FWO), 180 KJ/mol (Friedman), 177 KJ/mol (Vyazovkin), and 174 KJ/mol (Cai).